Fun Ride: Healthy and Sustainable Lifestyle - MOHD FAUZI, MUHAMMAD AIMAN BIN; OMAR, AFIQ HAIKAL BIN; YUSRI, KHAIRUNNISAA BINTI (Multidisciplinary Applied Research and Innovation, 2022)
A project has been carried out that is Fun Ride for Healthy Lifestyle and Electricity to meet the needs of the community, especially during the Covid-19 pandemic season where everyone sits at home with family and wants to spend their time with beneficial activities such as sports. Next, this project is also carried out to meet the requirements of the Final Year Project, Diploma in Electrical Engineering. This study aims to provide fun to all communities at the same time it can also keep the body healthy even just by cycling. This is in line with the current situation where Malaysians are constrained to leave home. Therefore, this cycling sport will be able to help in ensuring that all users can carry out sporting activities without having to go out of the house and without worrying about the prevalent infectious diseases at this time. However, the busyness of some people working all the time in their daily activities can affect their health care. The technology of this project can help them keep their body healthier with simple exercises that can be done at any time. It will not bother them to perform other daily activities. This is in line with the development of innovations developed through projects in a number of institutions. In conclusion, this system can help reduce the rate of obesity in our country and it can also ensure that the community can engage in sports activities while having fun during the Covid-19 pandemic.